Determination of Osteoporosis Risk in Post-Menopausal Women Using the Malaysian Osteoporosis Screening Tool: A Pilot Study in a Community Pharmacy - Athirah Ahmad Latif; Nursyuhadah Othman; Saliha Azlan; Nik Ateerah Rasheeda Mohd Rocky; Siti Sarah Syahirah Kushairi; Nik Aisyah Najwa Nik Mustaffa Shapri; Mohd Shahezwan Abd Wahab (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Osteoporosis detection remains suboptimal in Malaysia. This study aimed to evaluate osteoporosis risk using the Malaysian Osteoporosis Screening Tool (MOST) and supplementation behaviors in a community pharmacy. A cross-sectional study was conducted in a private pharmacy in Temerloh, Pahang (May–August 2025). Postmenopausal women (n = 126) completed questionnaires and underwent anthropometric assessment (BMI, hip circumference). MOST scores were calculated, and group differences were analyzed using Mann–Whitney U and Kruskal–Wallis tests (p <0.05). All participants were classified as